Motivation for TV white space: An explorative study on Africa for achieving the rural broadband gap - Miquel Oliver; Sudip Majumder (International Telecommunications Society (ITS), 2019)
Emergence of digital broadcasting is the key index of the new horizons of communication and media environment. In this paper we will discuss how TVWS, the resultant of digital switchover is approaching for becoming a financially rewarding solution in terms of rural areas than the other cellular technologies i.e 3G and 4G or even for upcoming 5G. We will analyze the standpoint of digital switchover around the globe and will try to the look at the white space capacity. There has been several TVWS pilot testing all over the world, specially in Africa region and we will try to evaluate their inclusive performance as they match the needs to deploy mobile broadband in rural and low-density areas. After shortly presenting the case, we will try to measure the potential of TVWS technology in terms of the other regions around the world which share the same teletraffic profile and socio-economic condition. Also we will try to present the importance of regulatory issues with ICT strategies and market development with propos
Keywords: 330